Physicochemical Properties Of Reforming The Recycled Biobased Polylactic Acid (pla) Filament Into Film-liked Shape - Nuradlyna Safyah Mohd Rozi; Muhammad Naqib Hamdan; Amir Mustaqim Mohd Naim; Mohd Shaiful Sajab; Hatika Kaco (AIP Publishing, 2025)
Indexed Publication (Tier 2)